2017
DOI: 10.1083/jcb.201512012
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional determinants of tolerogenic and immunogenic states during dendritic cell maturation

Abstract: Dendritic cells promote either immunosuppressive or immunogenic T cell responses, but the transcriptional and epigenetic programs regulating these functions are unclear. Vander Lugt et al. dissect the distinct programs underlying the immunogenic and tolerogenic mature states of dendritic cells in vitro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
70
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 79 publications
(75 citation statements)
references
References 48 publications
5
70
0
Order By: Relevance
“…Interestingly, Aldh1a2 was one of the highly expressed genes in PD-L2 + BMDCs (23). A recent study regarding conditional deletion of the Irf4 gene in CD11c + DCs showed that the development of tolerogenic DCs possessing the expression and the enzymatic activity of RALDH2 is diminished (24). In the current study, to distinguish the development process and the gene regulation of DCs, we used the knockdown experiments using siRNA against GM-CSF-derived BMDCs and Flt3L-BMDCs at the later stage of development and elucidated the mechanism of cell typespecific transcription of Aldh1a2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, Aldh1a2 was one of the highly expressed genes in PD-L2 + BMDCs (23). A recent study regarding conditional deletion of the Irf4 gene in CD11c + DCs showed that the development of tolerogenic DCs possessing the expression and the enzymatic activity of RALDH2 is diminished (24). In the current study, to distinguish the development process and the gene regulation of DCs, we used the knockdown experiments using siRNA against GM-CSF-derived BMDCs and Flt3L-BMDCs at the later stage of development and elucidated the mechanism of cell typespecific transcription of Aldh1a2.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we found that the expression of IRF4 and the binding of PU.1 to the Aldh1a2 promoter were enhanced in GM-CSF-stimulated cells, in which the Aldh1a2 transcription was markedly increased. Considering that the IRF4 level in RALDH2-positive DCs is higher than those in other DCs in vivo (18,23,24), the binding degree of PU.1 and IRF4 may be associated with the potential for transcription of the Aldh1a2 gene.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the presence of microbial products, DCs mature and activate nuclear factor kB, which facilitates the generation of effector T cells and an immunogenic profile. 58 Interestingly, the maturation state of DCs can be affected by their interaction with different types of cancer cells. Steady-state immature DCs are maintained and suppressed by cancer cells in a tumor and are also referred to as tumor-infiltrating DCs.…”
Section: Dcsmentioning
confidence: 99%
“…To explore if IRF4 along with its ETS and AP-1 family partners, PU.1 and BATF3 could be directly controlling the expression of antigen cross-presentation genes in human LCs, we performed genome-wide chromatin profiling and transcription factor motif enrichment analyses. This approach enables the inference of transcriptional regulatory sequences and the transcription factors that are acting to control gene activity in distinct cell types and cell states 39,57 . Notably, tri-methylation at lysine 4 of histone 3 (H3K4Me3) marks active promoters 58 , whereas acetylation of lysine 27 of histone 3 (H3K27Ac) marks active transcriptional enhancers; the latter have been postulated to be the primary determinants of tissue-specific gene expression 59,60 .…”
Section: Enrichment Of Irf Composite Elements In Chromatin Implicatesmentioning
confidence: 99%
“…IRF4 and IRF8 are critical for all aspects of DC biology, controlling a wide range of functions. These include induction of innate responses elicited via pattern recognition receptors TLR, NOD, and RIG during viral and bacterial infection [36][37][38] , cell activation, and efficient antigen uptake, presentation and cross-presentation 23,33,39 , migration and tolerance induction 39,40 . Interestingly, it has been postulated that the ability of murine DC subsets to efficiently activate CD8 and CD4 T cells, depending on the presentation of antigen in the context of MHC class I and II, is determined by the relative expression of IRF8 and IRF4, respectively 33 .…”
Section: Introductionmentioning
confidence: 99%